ANALISIS PENGARUH PENGETAHUAN DAN SIKAP PETANI TERHADAP PERILAKU PETANI DALAM PENINGKATAN KUALITAS LINGKUNGAN DI KECAMATAN CAMPALAGIAN KABUPATEN POLEWALI MANDAR - Wahyuni, Uni; Ardi, Muhammad; Amir, Faizal (UNM Environmental Journals, 2023)
Agricultural land management can be seen from the behavior of farmers in managing and maintaining agricultural land. Farmers are reflected in how the behavior of farmers in cultivating and maintaining agricultural land. The behavior of farmers in the management of agricultural land that is environmentally sound will not lead to damage to the environment. This study aims to determine the effect of environmental knowledge and farmers' attitudes on farmer behavior in improving environmental quality in Campalagian District, Polewali Mandar Regency. This type of research uses descriptive qualitative research, simple regression analysis, and multiple regression. The sample in this study was 88 heads of families living around the Botto Village area, Campalagian District. The results showed that environmental knowledge and community attitudes were in the high category to support farmer behavior in improving environmental quality in the Sekka-sekka Irrigation Area.